2011
DOI: 10.1107/s1600536811037354
|View full text |Cite
|
Sign up to set email alerts
|

Ba11La4Br34: a new barium lanthanum bromide

Abstract: Key indicators: single-crystal X-ray study; T = 150 K; mean (La-Br) = 0.002 Å; disorder in main residue; R factor = 0.049; wR factor = 0.118; data-to-parameter ratio = 26.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In contrast, LaOI nanocrystals exhibit an amorphous background only after 3 days indicating the appearance of LaI 3 (orange asterisks) domains with prolonged exposure (Figure S1B). These results are further concordant with moisture uptake studies performed by Eagleman et al., which revealed that oxyhalides show considerably lower moisture uptake as compared to their halide counterparts [27] …”
Section: Resultssupporting
confidence: 91%
“…In contrast, LaOI nanocrystals exhibit an amorphous background only after 3 days indicating the appearance of LaI 3 (orange asterisks) domains with prolonged exposure (Figure S1B). These results are further concordant with moisture uptake studies performed by Eagleman et al., which revealed that oxyhalides show considerably lower moisture uptake as compared to their halide counterparts [27] …”
Section: Resultssupporting
confidence: 91%
“…: 850°C) 17) and insoluble nature in water (0.0035 g/100 g water ). 18) Although the LaOBr solid itself possessed the low electrical conductivity (ca. 10 ¹5 S•cm ¹1 at 800°C), we have realized the enhancement of the conductivity by replacing the La 3+ ion site in the LaOBr solid with lower valent Sr 2+ ion to form Br ¹ ion vacancies as a result of charge compensation.…”
Section: Introductionmentioning
confidence: 99%